(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
This paper discusses how loanwords in Uzbek – especially Russian/international and Arabic – Persian strata – should be handled in the linguistic front-end of text-to-speech (TTS) systems, using evidence from the Uzbek electronic corpus. The study aims to identify and systematize orthography – pronunciation mismatches that cause typical synthesis errors: bi-phonemic graphemes (the Uzbek letter <j> encoding both affricate and fricative realizations), homography driven by the lack of distinct letters for foreign phonemes (e.g., the letter <o> in certain borrowed forms), vowel sequences in loanwords that are realized with inserted glides (y/v), and stress- and syllable-structure-dependent variants. The methodology is based on descriptive analysis, phonetic – morphological interpretation, identification and analysis of typical word combinations in the electronic corpus, as well as a comparative approach to practical experiences in Turkish, Kazakh, and Tatar languages. The results propose a set of practical front-end strategies: enriched pronunciation lexicon for loanwords, context-based homograph disambiguation, explicit glide-insertion rules for vowel sequences, and curated exception lists for fricative-j items. Overall, corpus-driven linguistic normalization is argued to be the key factor for improving naturalness and reducing errors in Uzbek TTS.